Alpha and beta diversity of phytoplankton in two subtropical eutrophic streams in southern Brazil - Karling Fernanda Schuster; Priscila Izabel Tremarin; Gilza Maria de Souza-Franco (Acta Botânica Brasílica, 2015)
This paper reports the alpha and beta diversity of phytoplankton communities of two streams differing in land use. We analyzed which environmental conditions affect diversity of the phytoplankton communities and tested the hypothesis that stream stretches protected by forests will have lower species richness, whereas higher beta-diversity would occur among the non-protected stretches. Samples were taken quarterly, from February to November 2012, in nine stretches, including four non-protected stretches, two partially protected stretches and three totally forest-protected stretches. Eleven abiotic variables and their coefficients of variation were analyzed. Phytoplankton was analyzed for species richness (alpha diversity), frequency of occurrence and beta-diversity. Species richness was calculated by first and second order jackknife indexes. Biotic data were submitted to Sørensen similarity analysis. A total of 429 infrageneric taxa were reported, representing 88% of the estimated expected species richness. The phytoplankton composition was typical for lotic environments with high richness values of Bacillariophyceae (66.0%). High phytoplankton richness values occurred in all the sampled stretches, even though beta-diversity was moderate and indicated similarity between the sampled stretches, therefore only a part of the original hypothesis was corroborated.